Description of the advertisement calls of four species of Amazophrynella (Anura:Bufonidae) - Rojas, Rommel R.; de Carvalho, Vinicius Tadeu; Ávila, Robson W.; Kawashita-Ribeiro, Ricardo A.; Hrbek, Tomas; Gordo, Marcelo (Zootaxa, 2018)
Amazophrynella comprises 11 small bufonid species with a pan-Amazonian distribution (Fouquet et al. 2012a, b; Rojas et al. 2016, Rojas et al. 2018). All species inhabit the forest leaf litter, breed in seasonal puddles and are diurnally and nocturnally active (Fouquet et al. 2012b; Rojas et al. 2014; 2015; 2016). Until now only one nominal species, A. javierbustamantei, and two putative lineages—A. moisesii (Rio Yuyapichis, Peru) and A. siona (Santa Cecilia, Ecuador)—had their advertisement calls formally described (Duellman 1978; Schlüter 1981; Rojas et al. 2016). Herein, we described for the first time the advertisement calls from additional four species of Amazophrynella.